Arrhythmogenic Right Ventricular Dysplasia - a Variant of Primary Cardiomyopathy - G.E. Sukhareva; V.I. Sadovoy (Zaslavsky O.Yu., 2013)
This article provides an own observation of family form of arrhytmogenic right ventricular dysplasia in a girl, which had been followed-up for 12 years. Clinical manifestation of disease was life-threatening ventricular tachycardia, required the installation of cardioverter-defibrillator. Her mother also had ventricular tachycardia.